Establishment and characterization of new breast and ovarian cancer cell lines as a model for studying cellular plasticity in vitro - Bezdieniezhnykh, N.; Lykhova, A.; Semesiuk, N.; Okhrimenko, R.; Kudryavets, Yu. (Experimental Oncology, 2016)
Aim: To compare biological properties of primary tumor cells isolated from malignant effusion of cancer patients with the same cells of permanent lines established during their long-term cultivation in vitro and to assess the impact of phenotypic conversion that was caused by changes in their microenvironment on their behavioral characteristics. Materials and Methods: The study was performed on primary cell cultures from pleural effusion or ascites of breast and ovarian cancer and permanent cell lines derived from them, namely permanent ovarian cancer cell line I, permanent ovarian cancer cell line II and permanent breast cancer cell line I. Biological characteristics were studied using standard cell culture methods and immunocytochemical assays. Results: Three new cell lines were established from breast and ovarian cancer and cell morphology, migration activity, the kinetics of growth, colony forming activity in semisolid agar and sensitivity to anticancer drug were examined. These characteristics were compared with those of the primary tumor cells. It has been shown that among the primary tumor cells from malignant effusion, cells with mesenchymal characteristics were the most prevalent. Cultivation of primary cancer cells in vitro leads to a phenotypic change of their population: it becomes more homogeneous in morphology with predominantly epithelial-like cells. Also, later after a number of cell doublings in vitro, the cell population changes to include cells primarily with immunophenotypic properties characteristic of epithelial cells. These changes include increase in number of E-cadherin-positive cells and a decrease in number of vimentin and α- smooth muscle actin-positive cells. It was found that significant changes in expression of epithelial-mesenchymal transition associated proteins in cells during their cultivation in vitro in new microenvironment are accompanied by a rapid change in their sensitivity to anticancer drugs. Conclusions: The new breast and ovarian cancer cell lines were established and characterized. The induction of phenotypic transdifferentiation in malignant cells from pleural effusion and ascites can be an important approach for suppressing the progression of neoplastic process.